Isolated yeasts from bioferments of mountain microorganisms, an option for plant nutrition - Mora-López, Marcela (2023)
Introduction. Phosphorus and potassium are essential nutrients for plant development; however, they are scarcely available in soil, making chemical or mineral fertilization necessary, an inefficient practice due to the absence of solubilizing microorganisms. The application of Mountain Microorganisms (MM) bioferments is an alternative, however, few studies show the agronomic potential of the yeasts present in this type of bioferments. Objective. To evaluate, at in vitro level, the biofertilizing and growth-promoting capacity of antagonist yeasts isolated from MM bioferments. Materials and methods. This research was carried out in 2019 at the University of Medellín, Colombia. The biofertilizing capacity was determined by measuring the solubilization of phosphorus and potassium in solid media by measuring the solubilization halos and in a liquid medium by quantifying phosphorus (PS) and soluble potassium (KS) in mg per liter of soluble mineral. The growth-promoting activity was determined by quantifying the production of acetic indole (AIA) of yeasts isolated from MM. As an additional test, the production capacity of cellulases was evaluated in a carboxymethyl cellulose (CMC) media. Results. On day six, the highest concentrations of PS and KS in liquid medium were evidenced. Both in NBRIP agar and broth with P rock, the isolate GRB-LB05 showed a PS of 3.57 mg L-1 different from the control. In modified NBRIP agar and feldspar broth, GRB-LB01 had the lowest pH and a low KS concentration, while GRB-LB12 (1.32 mg L-1) and GRB-LB02 (1.12 mg L-1) registered the highest concentrations of KS. GRB-LB06 yeast was the most promising IAA-producing isolate (12 mg L-1), followed by GRB-LB13. Conclusions. The antagonistic yeasts isolated from liquid MM bioferments showed biofertilizing and growth-promoting capacity, with GRB-LB12 (Suhomyces xylopsoci) being the one that stands out in the solubilization of P, K, IAA production and cellulolytic capacity.